1994
DOI: 10.1002/j.1460-2075.1994.tb06232.x
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal domain of a rab protein is involved in membrane-membrane recognition and/or fusion.

Abstract: Proteins of the YPT1/SEC4/rab family are well documented to be involved in the regulation of membrane transport. We have previously reported that rab5 regulates endosome-endosome recognition and/or fusion in vitro. Here, we show that this process depends on the rab5 N-terminal domain. Treatment of early endosomal membranes at a low trypsin concentration essentially abolished fusion and cleaved rab5 to a 1 kDa smaller polypeptide. Two-dimensional gel analysis suggested that rab5 is one of the few, if not the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 70 publications
4
34
0
Order By: Relevance
“…Although the isoprenylated C-terminal motif is required for membrane targeting (66,67), functions of the extreme N-terminal region are still unknown. Given that deletion of the first 14 -22 amino acid residues at the N-terminal domain alone is enough to disrupt Rab5a functionalities (42), the N-terminal region is not only an important element for Rab5a function; it might also act as the domain that specifies isoform functionality. Taking it a step further, we have shown that when phosphorylation of Rab5a on the N-terminal Thr-7 site is disrupted, T-cell migration through ICAM-1-coated membranes toward SDF-1␣ is significantly repressed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the isoprenylated C-terminal motif is required for membrane targeting (66,67), functions of the extreme N-terminal region are still unknown. Given that deletion of the first 14 -22 amino acid residues at the N-terminal domain alone is enough to disrupt Rab5a functionalities (42), the N-terminal region is not only an important element for Rab5a function; it might also act as the domain that specifies isoform functionality. Taking it a step further, we have shown that when phosphorylation of Rab5a on the N-terminal Thr-7 site is disrupted, T-cell migration through ICAM-1-coated membranes toward SDF-1␣ is significantly repressed.…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed essentially as described [20,31]. Briefly BHK cells were allowed to internalize avidin or biotinylated horseradish peroxidase (bHRP).…”
Section: 8 In Vitro Fusion Of Early Endosomesmentioning
confidence: 99%
“…The C-terminal domain functions in targeting the protein to the early endosomes but it is not sufficient to confer Rab5a function [34,37]. The Nterminus and the regions predicted to undergo nucleotidedependent conformational changes (the effector domain or switchl, ~2/L5 or switch2 and ct3/L7) are additionally required for the regulatory role of Rab5a in endocytic transport [31,37]. Ca-Rab5a…”
Section: Molecular Cloning Of Rab5b and Rab5c Cdnasmentioning
confidence: 99%
“…The synthetic protein binds endogenous GDP (40); limited digestion of this GDP-bound form with trypsin produces a single 35 S-labeled fragment of 14 kDa. Addition of 30 mM EDTA to chelate Mg 2ϩ essential for guanine nucleotide binding markedly reduces the amount of the latter tryptic peptide.…”
Section: S-labeled Rab5mentioning
confidence: 99%
“…Important functional roles of the N-terminal domains of several Ras-like GTP-binding proteins also have been noted in studies of guanine nucleotide exchange (33)(34)(35)(36)(37)(38). Myristoylation at the N terminus of ARF enhances its rate of GDP release (27), and N-terminal truncation of ARF results in loss of function by reducing its affinity for GDP and permitting GDP/GTP exchange in the absence of phospholipids (33).…”
mentioning
confidence: 99%